2019
DOI: 10.1167/iovs.18-26126
|View full text |Cite
|
Sign up to set email alerts
|

Meox2 Haploinsufficiency Accelerates Axonal Degeneration in DBA/2J Glaucoma

Abstract: PURPOSE. Glaucoma is a complex disease with major risk factors including advancing age and increased intraocular pressure (IOP). Dissecting these earliest events will likely identify new avenues for therapeutics. Previously, we performed transcriptional profiling in DBA/2J (D2) mice, a widely used mouse model relevant to glaucoma. Here, we use these data to identify and test regulators of early gene expression changes in DBA/2J glaucoma. METHODS.Upstream regulator analysis (URA) in Ingenuity Pathway Analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Although sex could influence many other physiological or pathological events, we found that sex had no significant effects on the anatomical parameters of the inner retina measured in this study. Others have previously reported that there are sex-specific differences in retinal gene expression in mice, including in microglial and RGC-specific pathways 57 , and some glaucoma studies using mice have detected sex-specific differences in disease 58,59 -which would seemingly be unrelated to the traits we have studied.…”
Section: Nishioka and Colleagues Studied Correlations Between Rgc Denmentioning
confidence: 71%
“…Although sex could influence many other physiological or pathological events, we found that sex had no significant effects on the anatomical parameters of the inner retina measured in this study. Others have previously reported that there are sex-specific differences in retinal gene expression in mice, including in microglial and RGC-specific pathways 57 , and some glaucoma studies using mice have detected sex-specific differences in disease 58,59 -which would seemingly be unrelated to the traits we have studied.…”
Section: Nishioka and Colleagues Studied Correlations Between Rgc Denmentioning
confidence: 71%
“…The DBA/2J mouse strain has been widely used as a model for ocular hypertension and glaucoma due to the presence of progressively worsening anterior chamber abnormalities and IOP increasing with age (Sheldon et al, 1995;Inman et al, 2006;Schlamp et al, 2006;Burroughs et al, 2011;Bosco et al, 2018;Mathieu et al, 2018;Buchanan et al, 2019;Jassim et al, 2019). In this study, we used strain-matched DBA/2J-Gpnmb + /SjJ mice to determine the relative contributions of corneal calcification and IPD to the apparent elevation of IOP characteristic of the DBA/2J mouse strain.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models of glaucoma are important to understanding the disease and identifying potential therapeutic strategies. The DBA/2J inbred mouse is one of the most widely used models of ocular hypertension-induced glaucoma and was first described as a model for glaucoma in 1995 (Sheldon et al, 1995;Inman et al, 2006;Schlamp et al, 2006;Burroughs et al, 2011;Bosco et al, 2018;Mathieu et al, 2018;Buchanan et al, 2019;Jassim et al, 2019). DBA/2J mice develop severe iris pigment dispersion (IPD), which causes elevated intraocular pressure (IOP) as a result of occluded aqueous humor drainage pathways (John et al, 1998;Libby et al, 2005;Scholz et al, 2008).…”
Section: Introductionmentioning
confidence: 99%